Emerging Trends in Injectable Stimuli‐Responsive Hydrogel Microspheres: Design Strategies and Therapeutic Innovations - Jiacheng Liu; Chengcheng Du; Senrui Liu; Junyan Liu; Xuefeng Luo; Jingdi Zhan; Zhuolin Chen; Zhenglin Zhu; Liangbin Zhou; Zhong Alan Li; Wei Huang; Yiting Lei (MedComm – Biomaterials and Applications)
ABSTRACT Hydrogels, as three‐dimensional hydrophilic polymer networks, have been widely utilized in biomedical applications due to their excellent biocompatibility, high water content, and tunable physicochemical properties. However, traditional bulk hydrogels often suffer from limitations such as inadequate mechanical strength, slow response to external stimuli, and restricted diffusion efficiency, which hinder their performance in dynamic biological environments. To overcome these challenges, hydrogel microspheres (HMs) have emerged as a promising alternative, which offers advantages such as injectability, high surface‐area‐to‐volume ratio, and tunable functionality. By integrating natural and synthetic materials with advanced fabrication techniques, including microfluidics and emulsification, researchers have achieved precise control over the morphology, size, and bioactivity of HMs. In recent years, stimuli‐responsive HMs have attracted significant attention for their ability to respond intelligently to environmental cues such as pH, reactive oxygen species (ROS), enzymes, and temperature. This enables controlled drug release, enhanced therapeutic precision, and spatiotemporal regulation in biomedical applications. This review systematically summarizes the materials, fabrication strategies, and functional mechanisms of stimuli‐responsive HMs, highlighting their applications in drug delivery, disease treatment, and tissue engineering. Furthermore, key challenges and future perspectives are discussed, which provides insights into how these intelligent HMs can advance personalized medicine and clinical translation.